Gender Equity in Ethnoscience Learning: Evidence from Preservice Teachers’ Perceptions - Ali Imran; Siti Rahma Yunus (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study examines gender-based differences in preservice biology teachers’ perceptions of ethnoscience-based learning, with particular attention to its potential to support equitable learning experiences. Grounded in the perspective of culturally responsive pedagogy, ethnoscience-based learning is assumed to foster inclusivity by integrating local knowledge into science instruction. This study employed a quantitative explanatory design with a cross-sectional approach, involving 28 participants selected through convenience sampling. Data were collected using a validated Likert-scale questionnaire measuring perceived learning quality, suitability to students’ ability levels, and learning motivation. The data were analyzed using descriptive statistics and an independent-samples t-test. The results indicate that ethnoscience-based learning was generally perceived positively, with a moderate-to-high overall mean score (M = 2.98 on a 4-point scale). Male (M = 3.13) and female (M = 2.91) participants reported similarly favorable perceptions. However, the independent-samples t-test revealed no statistically significant difference between the two groups (p = 0.116 > 0.05). These findings suggest that perceptions of ethnoscience-based learning tend to be consistent across gender groups, although such results should be interpreted cautiously given the limited sample size. From a gender perspective, the absence of significant differences in perception indicates a comparable level of perceived learning experience among male and female students, rather than confirming the full realization of gender equity. The findings highlight the potential of ethnoscience-based learning as an inclusive instructional approach, while also emphasizing the need for further investigation using broader samples and more comprehensive indicators of equity, such as participation, access, and learning outcomes. This study contributes to the growing discourse on culturally responsive and gender-sensitive practices in science teacher education